SIMULATION AND ANALYSIS OF VEHICULAR AD-HOC NETWORKS IN URBAN AND RURAL AREAS - Mohammed Ali, Hayder (My University, 2014)
According to the American National Highway Traffic Safety Administration, in 2010, there were an estimated 5,419,000 police-reported traffic crashes, in which 32,885 people were killed and 2,239,000 people were injured in the US alone. Vehicular Ad-Hoc Network (VANET) is an emerging technology which promises to decrease car accidents by providing several safety related services such as blind spot, forward collision and sudden braking ahead warnings. Unfortunately, research of VANET is hindered by the extremely high cost and complexity of field testing. Hence it becomes important to simulate VANET protocols and applications thoroughly before attempting to implement them. This thesis studies the feasibility of common mobility and wireless channel models in VANET simulation and provides a general overview of the currently available VANET simulators and their features. Six different simulation scenarios are performed to evaluate the performance of AODV, DSDV, DSR and OLSR Ad-Hoc routing protocols with UDP and TCP packets. Simulation results indicate that reactive protocols are more robust and suitable for the highly dynamic VANET networks. Furthermore, TCP is found to be more suitable for VANET safety applications due to the high delay and packet drop of UDP packets.
Keywords: vehicular ad-hoc networks; routing protocols; TCP; UDP; mobility models; wireless channel models; simulation; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|